MAKING SIMPLE HYDROPONICS TO IMPROVE STUDENTS’ SCIENCE-PROCESS SKILLS IN PGSD DEPARTMENT FKIP UMSU - Indah Pratiwi; Chairunnisa Amelia; Karina Wanda (UIN Sumatera Utara Medan, 2021)
This study aims to determine the process of planting and growing mustard bok choy through hydroponics. Hydroponics is a system of cultivating plants without using soil as a medium for growing plants. Provision of nutrients needed for hydroponic cultivation of plants, essential nutrients both macro, and micro. Bok choy is a plant that has high economic value. The planting of bok choy mustard is carried out in Tanjung Balai City, Teluk Nibung District, Struggle Village. The process of planting mustard bok choy is carried out in the area where the researcher lives in June due to the impact of the COVID-19 pandemic. The time for planting mustard bok choy is carried out for approximately 40 days until the harvest. The interaction between the concentration of nutrients and the type of mustard affects the growth of mustard bok choy. The nutrients used for planting mustard bok choy are AB Mix nutrients. This study showed that the concentration of AB Mix nutrients given to the growth of mustard bok choy grew hydroponically